Strategic plan for the Caribbean Community 2015-2019 : repositioning CARICOM. Vol. 1 : The Executive plan (CARICOM Secretariat GeorgetownGY, 2014)
Outlines the strategic repositioning of the Community, and captures a development agenda going forward that encompasses: a review of development needs; a resilience model for socio-economic progress; strategies to renew the commitment to and strengthen actions for enhancing regional unity; and an agenda for the reform of governance mechanisms to achieve these thrusts.
Keywords: CARICOM